2022
DOI: 10.1101/2022.01.04.22268750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-mediated and humoral immune response to SARS-CoV-2 vaccination and booster dose in immunosuppressed patients

Abstract: Importance: Data on the humoral and cellular immune response to primary and booster SARS-CoV-2 vaccination in immunosuppressed patients is limited. Objective: To determine humoral and cellular response to primary and booster vaccination in immunosuppressed patients and identify variables associated with poor response. Design: Retrospective observational cohort study. Setting: Large healthcare system in Northern California. Participants: This study included patients fully vaccinated against SARS-CoV-2 (mRN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our main finding is, thus, that after a third dose of SARS-CoV-2 mRNA vaccines, only a subset of patients mounts a humoral immune or CMI response. Emerging reports by others have found a similar rate of around 25% de novo antispike seroconversion after a third dose of SARS-CoV-2 vaccines in patients on anti-CD20 therapies that were humoral non-responders after a two-dose vaccination scheme 8–10 18–23. Several studies that used EliSpot or activation-induced markers to semiquantitatively assess CMI revealed higher rates of CMI than humoral responses after a third SARS-CoV-2 vaccine in patients with autoimmune diseases under anti-CD20 treatment 8 19 24–26.…”
Section: Discussionmentioning
confidence: 83%
“…Our main finding is, thus, that after a third dose of SARS-CoV-2 mRNA vaccines, only a subset of patients mounts a humoral immune or CMI response. Emerging reports by others have found a similar rate of around 25% de novo antispike seroconversion after a third dose of SARS-CoV-2 vaccines in patients on anti-CD20 therapies that were humoral non-responders after a two-dose vaccination scheme 8–10 18–23. Several studies that used EliSpot or activation-induced markers to semiquantitatively assess CMI revealed higher rates of CMI than humoral responses after a third SARS-CoV-2 vaccine in patients with autoimmune diseases under anti-CD20 treatment 8 19 24–26.…”
Section: Discussionmentioning
confidence: 83%
“…The screening process is illustrated in the PRISMA flowchart in Figure 1 . Of these studies, there were 12 observational studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], one randomised-controlled trial [ 33 ], and four case series [ 34 , 35 , 36 , 37 ]. The key trial characteristics of each included study are reported in Table 1 , with a comparison of the characteristics of the studies included in the meta-analysis in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 booster vaccines administered in the studies included mRNA (Pfizer-BioNTech, BNT162b2 and Moderna, mRNA-1273) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 , 37 ], non-replicating viral vector (AstraZeneca, AZD1222 and Janssen, Ad26.COV2.S) [ 21 , 28 , 29 , 30 , 34 , 35 , 36 , 37 ], protein subunit (Novavax, NVX-CoV2373) [ 33 ] and inactivated (Sinovac, CoronaVac) vaccines [ 35 ]. Bonelli et al involved two cohorts receiving mRNA vaccines as the primary series, but one received heterologous AstraZeneca booster doses while the other received homologous mRNA boosters [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 1 study, use of immunosuppression in patients with autoimmune disease resulted in 1. 35-fold (95% CI, 1.29-1.40) greater odds of developing life-threatening .…”
Section: Introductionmentioning
confidence: 99%